PEMUNGUTAN PAJAK REKLAME DAN KONTRIBUSINYA TERHADAP PENERIMAAN PAJAK DAERAH (STUDI KASUS PADA DINAS PENDAPATAN PENGELOLAAN KEUANGAN DAN ASET (DPPKA) KABUPATEN MALANG) - Kusumawati, Irine (Jurnal Mahasiswa Perpajakan, 2015)
Local government must seek the sources of revenue to finance its local development. One of local revenue sources was local tax. Several kinds of tax may be collected to improve local tax revenue. Billboard tax is a local tax with great potential to improve local tax revenue and also to provide great contribution to local tax revenue. The objectives of research are to understand growth rate of billboard tax and local tax, and to recognize the contribution of billboard tax to local tax in Malang District. The result of this research will be expected to provide beneficial and advantages for Local Government especially The Office of Income, Financial Management and Asset. Data based on the billboard tax and local tax revenues for 5 years period of 2009 to 2013. Keyword: Billboard tax, Contribution, Local Tax Revenue